FORMULATION OF SERUM GEL CONTAINING ANGELICA KEISKEI LEAF EXTRACT AS AN ANTIOXIDANT AND TYROSINASE ENZYME INHIBITOR - AULIFA, DIAH LIA; NOERFITRI, RIZKA Y.; TRISTIYANTI, DEBY; BUDIMAN, ARIF (International Journal of Applied Pharmaceutics, 2020)
Objective: The aim of this study was to formulate and evaluate the efficacy of Angelica keiskei (AK) leaf extract in serum gel as an antioxidant and tyrosinase enzyme inhibitor. Methods: The leaves of AK were extracted using the maceration method, while the antioxidant and tyrosinase enzyme inhibitory activities were determined using 1,1-diphenyl-2-picrylhydrazyl (DPPH) and L-Tyrosine as assay and substrate, respectively. Subsequently, the extract was formulated into serum gel and evaluated for physical stability, antioxidant and inhibitory activity to tyrosinase enzyme. Results: The results showed that AK leaf extract has antioxidant activity, with an IC50 value = 7.73 mg/ml, while the tyrosinase enzyme inhibitory power had an IC50 value = 500 mg/ml. Based on physical stability, the serum gel was stable after 28 d of storage. The serum gel of AK leaf extract also showed antioxidant activity and tyrosinase enzyme inhibition with IC50 value of 16.68 mg/ml and 741.62 mg/ml, respectively. Conclusion: This study demonstrated that the serum gel of AK leaf extract has potential as a skin lightening agent and is safe for use as a topical preparation.